2007
DOI: 10.1002/pssb.200642514
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of polycrystalline TiO2 at elevated temperatures. Electrical conductivity

Abstract: IN MEMORIAM. This paper is dedicated to the memory of Dr. J. Bruce Wagner, Jr. (1926–2006), long time Professor of Materials Science and Engineering at the Northwestern University, Evanston, IL and Regents Professor of the Arizona State University, Tempe, AZ. Professor Wagner was prominent scientist in the area of solid‐state science, electrochemistry and high temperature chemistry. He served as Director of the Material Research Centre at the Technological Institute of Northwestern University, Director of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(91 citation statements)
references
References 27 publications
3
88
0
Order By: Relevance
“…The experiments were performed within several narrow ranges of p(O 2 ) to assess the changes of D chem with p(O 2 ). The experimental monitoring sheet showing the changes of oxygen activity, p(O 2 ), the temperature, T, and the electrical conductivity, σ , during reduction experiment at 1,273 K was reported before [17]. It was shown that imposition of a new p(O 2 ) results in instantaneous increase of p(O 2 ), which reaches its nominal value within 10 min.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The experiments were performed within several narrow ranges of p(O 2 ) to assess the changes of D chem with p(O 2 ). The experimental monitoring sheet showing the changes of oxygen activity, p(O 2 ), the temperature, T, and the electrical conductivity, σ , during reduction experiment at 1,273 K was reported before [17]. It was shown that imposition of a new p(O 2 ) results in instantaneous increase of p(O 2 ), which reaches its nominal value within 10 min.…”
Section: Methodsmentioning
confidence: 96%
“…The specimen and the experimental setup were described before [17,18]. Electrical conductivity was determined using high temperature Seebeck probe [19].…”
Section: Methodsmentioning
confidence: 99%
“…The electrical conductivity for polycrystalline specimen of undoped TiO 2 in oxygen, p(O 2 ) = 75 kPa, in the range 1073-1323 K, were reported elsewhere [31]. The specimens in the oxidising conditions were not studied during cooling since their conductance on cooling below 1073 K becomes unmeasurable.…”
Section: Undoped Tiomentioning
confidence: 99%
“…Isothermal changes of the electrical conductivity for high purity TiO 2 single crystal as a function of oxygen activity in the range 1073 -1323 K [31]. The data for high purity polycrystalline TiO 2 at 1273 K is also included.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation